Association of heterocellular HPFH, beta(+)-thalassaemia, and delta beta(0)-thalassaemia: haematological and molecular aspects. Issue 4 (August 1984) - Cianetti, L; Care, A; Sposi, N M; Giampaolo, A; Calandrini, M; Petrini, M; Massa, A; Marinucci, M; Mavilio, F; Ceccanti, M
Abstract : An Italian family in which heterocellular hereditary persistence of fetal haemoglobin (HPFH) interacts with both beta(+)- and delta beta-thalassaemia is described. The index case was an 8 year old girl who was presumed to inherit both heterocellular HPFH and beta (+)-thalassaemia from her mother and delta beta-thalassaemia from her father. She was healthy and never needed blood transfusions. The possible contribution of heterocellular HPFH to the less severe expression of the compound delta beta/beta(+)-thalassaemia heterozygosity is discussed. By DNA analysis the specific delta beta-thalassaemia defect on the gamma delta beta globin gene region has been established. In addition, a previously unreported association of a polymorphic restriction site haplotype with a beta (+)-thalassaemia mutation has been observed.